Brief Report: Single‐Cell Analysis Reveals Cell Division‐Independent Emergence of Megakaryocytes From Phenotypic Hematopoietic Stem Cells. (6th August 2015) - Roch, Aline; Trachsel, Vincent; Lutolf, Matthias P.
Abstract: Despite increasingly stringent methods to isolate hematopoietic stem cells (HSCs), considerable heterogeneity remains in terms of their long‐term self‐renewal and differentiation potential. Recently, the existence of long‐lived, self‐renewing, myeloid‐restricted progenitors in the phenotypically defined HSC compartment has been revealed, but these cells remain poorly characterized. Here, we used an in vitro single‐cell analysis approach to track the fate of 330 long‐term HSCs (LT‐HSC; Lin− cKit+ Sca‐1+ CD150+ CD48− CD34−) cultured for 5 days under serum‐free basal conditions. Our analysis revealed a highly heterogeneous behavior with approximately 15% of all phenotypic LT‐HSCs giving rise to megakaryocytes (Mk). Surprisingly, in 65% of these cases, Mk development occurred in the absence of cell division. This observation suggests that myeloid‐restricted progenitors may not derive directly from LT‐HSCs but instead could share an identical cell surface marker repertoire. Stem Cells 2015;33:3152–3157